Towards religious competence: diversity as a challenge for education in Europe - Heimbrock, Hans-Günter (Schriften aus dem Comenius-Institut, 2001)
Scholars around Europe reflect on the changing role of religious education in a time of growing pluralism in Europe and across the world. The various contributions from different European countries (England and Wales, Germany, Netherlands, and Norway) focus on the debate about the existing multicultural and multireligious situation in European societies. Difference and diversity, especially of religion, is seen as a challenge for education in Europe. The chapters mention trends and common challenges for religious education. As a key term of religious education "religious competence" is introduced. It includes the ability to deal with religious pluralism and differences in a constructive way. It is argued that contextual religious education facilitates a new religious competence. The readers get also detailed information about current developments in the field of religious education in some European countries. - Scholars around Europe reflect on the changing role of religious education in a time of growing pluralism in Europe and across the world. The various contributions from different European countries (England and Wales, Germany, Netherlands, and Norway) focus on the debate about the existing multicultural and multireligious situation in European societies. Difference and diversity, especially of religion, is seen as a challenge for education in Europe. The chapters mention trends and common challenges for religious education. As a key term of religious education "religious competence" is introduced. It includes the ability to deal with religious pluralism and differences in a constructive way. It is argued that contextual religious education facilitates a new religious competence. The readers get also detailed information about current developments in the field of religious education in some European countries. - Cok Bakker (Netherlands), Judith Everington (England), Leslie J. Francis (England), Elisabet Haakedal (Norway), Hans-Günter Heimbrock (Germany), Robert Jackson (England), William K. Kay (Wales), Heid Leganger-Krogstad (Norway), Thomas A. Lotz (Germany), Siebren Miedema (Netherlands), Eleanor Nesbitt (England), Sissel s̆tberg (Norway), Christoph Th. Scheilke (Germany), Peter Schreiner (Germany), Pat Sikes (England), Geir Skeie (Norway), Heinz Streib (Germany), Willem L. Wardekker (Netherlands)